1993
DOI: 10.1192/bjp.162.1.43
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clozapine on Cognition and Psychiatric Symptoms in Patients with Schizophrenia

Abstract: Psychiatric symptoms and cognition were assessed in 13 patients with schizophrenia, one patient with schizoaffective disorder, and one patient with psychosis not otherwise specified while they received a conventional neuroleptic and again after an average of 15 months on clozapine. Despite improvements in psychiatric symptoms, attention, memory, and higher-level problem-solving were essentially unchanged. This suggests that certain cognitive deficits are relatively independent of psychotic symptoms in schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
134
1
8

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(155 citation statements)
references
References 33 publications
12
134
1
8
Order By: Relevance
“…In this regard, the present study had the merits that it was conducted with a sufficient interval between assessments to avoid practice effects (Epstein et al 1996) and to assess within-subject changes in CPT performance across different states. Our finding that CPT performance is relatively independent of the severity of clinical symptoms is consistent with the most recently published studies using longitudinal designs with sufficient follow-up times and information processing paradigms (Cornblatt et al 1997;Epstein et al 1996;Finkelstein et al 1997;Goldberg et al 1993; Nuechterlein et al 1992). Furthermore, our results showed that the atypical neuroleptic risperidone did not improve patients' CPT performance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this regard, the present study had the merits that it was conducted with a sufficient interval between assessments to avoid practice effects (Epstein et al 1996) and to assess within-subject changes in CPT performance across different states. Our finding that CPT performance is relatively independent of the severity of clinical symptoms is consistent with the most recently published studies using longitudinal designs with sufficient follow-up times and information processing paradigms (Cornblatt et al 1997;Epstein et al 1996;Finkelstein et al 1997;Goldberg et al 1993; Nuechterlein et al 1992). Furthermore, our results showed that the atypical neuroleptic risperidone did not improve patients' CPT performance.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our results showed that the atypical neuroleptic risperidone did not improve patients' CPT performance. This finding is similar to those of studies that used traditional neuroleptics, and is consistent with a previous study of the effects of clozapine on cognition (Goldberg et al 1993). Despite the equivalence in CPT performance at baseline and no significant change from baseline to endpoint for both the risperidone and haloperidol groups, the undegraded CPT dЈ of the risperidone group was better than that of the haloperidol group.…”
Section: Discussionsupporting
confidence: 90%
“…Novel antipsychotic compounds (second-generation or 'atypical' antipsychotics) such as clozapine (Fitton and Heel, 1990), olanzapine (Fulton and Goa, 1997), and sertindole (Kane and Tamminga, 1997;Azorin et al, 2006) have some beneficial effect on negative symptoms and reduced potential to produce extrapyramidal side effects, but these agents have demonstrated inconsistent effects on cognitive function in patients with schizophrenia. Depending on the type of cognitive domain measured, second-generation antipsychotics have been reported to produce improvement (Mortimer 1997;Meltzer and McGurk, 1999;Keefe et al, 2007), no effect (Hoff et al, 1996;Meltzer and McGurk, 1999), and impairment (Goldberg et al, 1993). The effect of sertindole on cognitive function has not been investigated extensively; however, a small clinical trial indicates a beneficial effect on some cognitive substrates, including executive function, in individuals diagnosed with schizophrenia (Gallhofer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of people with schizophrenia have shown clozapine-induced cognitive improvements in attentional tasks (Gallhofer et al, 1996;Hagger et al, 1993;Lee et al, 1999;Manschreck et al, 1999;Meltzer and McGurk, 1999;Sharma and Mockler, 1998). Other clinical studies, however, have demonstrated clozapine-induced memory deficits (Goldberg et al, 1993;Goldberg and Weinberger, 1996). Furthermore, rodent studies have shown clozapine-induced memory impairments in intact rats Skarsfeldt, 1996).…”
Section: Introductionmentioning
confidence: 99%